Can dosimetry affect local control and survival in patients with early-stage lung cancer treated with Stereotactic Ablative Radiotherapy (SABR)? An analysis of the UK's largest cohort of lung SABR patients. (3rd April 2021) - Saha, Animesh; Beasley, Matthew; Hatton, Nathaniel; Dickinson, Peter; Franks, Kevin; Clarke, Katy; Jain, Pooja; Teo, Mark; Murray, Patrick; Lilley, John
Abstract: Purpose/objectives: A recent study has shown that tight conformity of lung Stereotactic Ablative Radiotherapy (SABR) plans might worsen loco-regional control and can predict distant metastases. The study aims to report overall survival (OS), progression-free survival (PFS), local recurrence free survival (LRFS), and dosimetry of early-stage lung cancer patients treated with SABR and to try to explore any dosimetric predictor of outcomes. Material and methods: Patients treated in our institute (May 2009–August 2018) were included. Electronic medical records were reviewed for baseline characteristics, treatment details, and outcomes. Dosimetric data were extracted from Xio and Monaco software. Patients were treated according to the United Kingdom (UK) SABR consortium guidelines. Kaplan–Meier's analysis with log-rank test was used for survival analysis. The univariate and multivariable Cox regression model was used for correlating dosimetric variables and outcomes. Results: We treated 1266 patients with median age of 75 years and 47.4% were male. Median follow up was 56 months. Median OS was 36 months with 1, 2, and 5 years OS of 84.2%, 64.5%, and 31.5%, respectively. Median for PFS and LRFS was not reached. One, 2, and 5 years PFS were 87.4%, 78.4%, and 72.5%, respectively. One, 2, and 5 years LRFS were 98.2%, 95.1%, and 92.5%, respectively. Planning target volume (PTV), dose to 99% volume of PTV (D99), and R50 (volume receiving the 50% dose/volume (PTV)) were significantly associated with OS. PTV, mean lung dose (MLD), V20 (volume of lung minus gross tumour volume (GTV) receiving 20 Gy), V12.5 (volume of lung minus GTV receiving 12.5 Gy), and dose fractionation were significantly associated with PFS. Nothing was associated with LRFS on univariate analysis. R100 of >1.1 was associated with better OS, PFS, and LRFS compared to R100 ≤ 1.1. Conclusion: SABR achieves good clinical outcomes in patients with early-stage lung cancer; even in elderly patients with multiple comorbidities. In the largest UK early lung cancer cohort treated with SABR, we found that dosimetry correlates with clinical outcomes. Further validation of these results is needed to guide future optimisation of SABR delivery.